Crédits aux particuliers - Analyse des données de la Centrale des Crédits aux Particuliers - Helga De Doncker (National Bank of Belgium, 2006)
– Since 1 June 2003 the file of the Central Office for Credits to Private Individuals has recorded information relating to all consumer credits and mortgage loans contracted by natural persons for private purposes, as well as any payment defaults resulting from these loans. This registration aims to strengthen the means of preventing the excessive indebtedness of private individuals. In this paper the data of this unique and quasi exhaustive database are thoroughly analysed. Based on the information for the registered credit contracts and the registered persons, firstly a general description of the structure and characteristics of the Belgian private credit market is given. Further, the paper investigates borrowing and payment behavior according to debtor characteristics. The study finds that borrowing patterns, especially as credit portfolio composition is concerned, clearly diverge according to age and residence. Furthermore, striking differences were found for the percentage of loan defaults if these variables were taken into account. In particular, the paper comes to the conclusion that loan defaults aggregated at the regional level show remarkably strong correlations with economic and demographic factors.
Keywords: D14; D18; G21; G22; G29; R29; 330; credit bureau; consumer credits; mortgage loans; loan payment defaults; Verbraucherkredit; Hypothek; Private Verschuldung; Kreditmarkt; Belgien